Prediction of Public Opinion by School Trustees and Professional Educators - Brosseau, John F.; Zingle, Harvey (Canadian Journal of Counselling and Psychotherapy, 2012)
This study sought to determine whether or not job affiliation,life orientation, or biographical factors correlated with ability to predictpublic opinion on educational issues. When a group of trustees and four groups of professional educators were compared it was discovered that school counsellors were better predictors of public opinion than either teachers or school principals. The implication of this study is that educators wishing to get a reading of public opinion on educational matters should consult counsellors in their schools.